ANALISIS PERBEDAAN USAHATANI BERBAGAI VARIETAS PADI SAWAH TADAH HUJAN DI KECAMATAN BANGKINANG KABUPATEN KAMPAR - Jamalludin Jamalludin (Fakultas Pertanian, Universitas Riau, 2020)
The purpose of this research is to know the difference of production, income and efficiency of rainfed rice farming system of national superior varieties, local superior varieties and hybrids in Kecamatan Bangkinang Kampar District. This research uses survey method. The sampling technique of rainfed lowland rice farmer is done by using Malti Stake Sampling method. And the number of farmers as many as 90 people. Analysis of differences of farming varieties of rainfed lowland rice varieties have differences, but need to be tested again the hypothesis there are differences or not, To test the hypothesis on how much difference and the influence of various varieties of rainfed rice paddy to production, income and efficiency of rice used analysis of variance anova) single factor by using anova program on microsoft excel. There is a difference in the production of rainfed lowland rice between use of IR 42, Daro and Super Bernas varieties, at a 99% confidence level or at α 0.01. The income and efficiency of rainfed lowland rice farming between the use of IR 42, Daro and Super Bernas varieties did not differ significantly, with a 99% confidence level or at α 0.01. While the income and efficiency of farming there are significant differences.